(untitled) (Asian Business Research, 2022)
Leader humor in workplace can change the working state of subordinates. However, existing empirical studies have failed to determine whether the effect of positive and negative leader humor on the working status of subordinates is normal, or whether the effect of leader humor in profit and non-profit organizations or under Eastern and Western culture background is also different. To answer these questions, literature on the relationship between Leader humor and subordinate working status from 2009 to 2020 was searched, and 56 effect values of positive leader humor (a total of 16544 samples) and 24 effect values of negative leader humor (a total of 7781 samples) were obtained. The results of meta-analysis show that: (1)There is a significant positive relationship between positive leader humor and subordinates’ work status, while there is a significant negative relationship between negative leader humor and subordinates’ work status; (2) Positive leader humor promotes the subordinates’ behavior state improving by ameliorating their positive psychological state or attitude state in the workplace; (3)Negative leader humor inhibits the subordinates’ behavior state improving by incurring their negative psychological state or attitude state in the workplace.